2017
DOI: 10.1038/s41598-017-14997-3
|View full text |Cite
|
Sign up to set email alerts
|

Injection of high dose botulinum-toxin A leads to impaired skeletal muscle function and damage of the fibrilar and non-fibrilar structures

Abstract: Botulinum-toxin A (BoNT/A) is used for a wide range of conditions. Intramuscular administration of BoNT/A inhibits the release of acetylcholine at the neuromuscular junction from presynaptic motor neurons causing muscle-paralysis. The aim of the present study was to investigate the effect of high dose intramuscular BoNT/A injections (6 UI = 60 pg) on muscle tissue. The gait pattern of the rats was significantly affected 3 weeks after BoNT/A injection. The ankle joint rotated externally, the rats became flat fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 73 publications
5
71
1
Order By: Relevance
“…Studies using BoNT/A have largely involved safety assessments via potency tests in laboratory animals. In addition, studies addressing mechanism and phenotype of muscle change have been reported, including those evaluating dose-dependent responses to BoNT/A muscle injection [23]. Research using laboratory animals with rodent has long been conducted on basic research and treatment of human diseases and on the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using BoNT/A have largely involved safety assessments via potency tests in laboratory animals. In addition, studies addressing mechanism and phenotype of muscle change have been reported, including those evaluating dose-dependent responses to BoNT/A muscle injection [23]. Research using laboratory animals with rodent has long been conducted on basic research and treatment of human diseases and on the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…ICR mice, an outbred rodent model, have been previously used for the study of BoNT/A [24]. In previous rodent experiments, muscle change through the administration of BoNT/A muscle was found at various concentrations [23], but no comparative study has been conducted with ICR mice originating from different sources. The present study investigated the response to BoNT/A injection into muscle using mice from three different sources, Korl:ICR, A:ICR, and B:ICR.…”
Section: Discussionmentioning
confidence: 99%
“…botulinum toxin A injections, received by the participants might have influenced the results of this study. Some studies show microstructural changes at the tissue level in animals (Pingel et al, 2017) or have found an increase in muscle stiffness in in silico experiments (Wang, Gäverth, & Herman, 2018), whereas others report no changes in muscle stiffness (Alhusaini, Crosbie, Shepherd, Dean, & Scheinberg, 2011) after botulinum toxin A injections. Unfortunately, it is practically impossible to recruit a representative group of children with CP who have not had any interventions during their life.…”
Section: Discussionmentioning
confidence: 99%
“…This process inhibits nerve signalling, leading to transient paralysis . Injecting BoNT‐A into muscle tissue prevents the extracellular release of acetylcholine due to protein degradation of SNAP25 and effectively leads to muscle paralysis …”
Section: Introductionmentioning
confidence: 99%